The Effect of Teacher Professionalism and Competency on the Quality of Education in the City of Langsa - Suhartini Suhartini; Sri Milfayetty; Arif Rahman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Improving teacher professionalism and competence is one of the main functions of the education and culture office as an effort to improve the quality of education in a region. This study looks at the influence of professionalism and competence of teachers in improving the quality of education in Langsa City. As for the sample, 50 Langsa public junior high schools, 2 Langsa public junior high schools and 50 Langsa public junior high schools 3 teachers were selected. The results showed that professionalism and competence simultaneously have a positive and significant effect on the quality of education in Langsa City because the value of Fcount> Ftable is (28,354> 2,960). Professionalism partially has a positive and significant effect on the Quality of Education in Langsa City because the value of tcount> ttable (2,212> 1,680). Teacher competence partially has a positive and significant effect on the quality of education in Langsa City because the value of tcount> ttable (54,939> 1,680).